Assessment of Serum Lipid Profile among Sudanese Patients with COVID-19 - E. Ali, Abdalla; K. Ibrahim, Hamsa; M. Dafalla, Abuagla; M. Abdalla, Hani M. Abdalla; Modawe, GadAllah (Journal of the Faculty of Medicine Baghdad, 2024)
Background: The COVID-19 pandemic has been linked to dyslipidemia in patients.Objective: To investigate the alterations in serum low-density lipoprotein (LDL)-cholesterol, high-density lipoprotein (HDL)-cholesterol, very low-density lipoprotein (VLDL), total cholesterol (TC), and triglycerides (TG) levels in individuals with COVID-19 infection.Cases and Methods: This study was conducted at Jabra Hospital, Khartoum state, Sudan, from February to September 2021. It was an analytical, controlled hospital-based study that involved a total of 136 subjects. Of these, 68 were Sudanese patients who had contracted COVID-19, while the other 68 were healthy individuals who served as the control group. Data was collected through a questionnaire, and the serum lipid profile was estimated using spectrophotometric methods through an enzymatic process. The data was analyzed using SPSS (V25).Results:  The study found that patients with COVID-19 had significantly lower levels of serum LDL, VLDL, TC, and TG compared to the control group.  The p-values for these differences were 0.001, 0.002, 0.000, and 0.001, respectively. There was no significant difference in serum HDL and BMI between the two groups. In the case group, serum lipid profiles (excluding HDL) were significantly higher in overweight individuals compared to those with normal weight. The p-values for these differences were 0.001, 0.002, 0.001, 0.001, and 0.001, respectively. However, there was no significant difference in serum HDL levels between the two weight groups. Interestingly, the serum lipid profile was significantly higher in overweight controls compared to the cases. The p-values for these differences were 0.001, 0.041, 0.024, 0.001, and 0.001, respectively. Lastly, the study found that the serum lipid profile was significantly lower among severe COVID-19 patients compared to the control group with a p-value of ≤0.001. In particular, serum LDL and TC were significantly lower in patients than controls, with p-values of ≤0.001 and 0.003, respectively. On the other hand, serum TG was significantly higher in cases than controls with a p-value of ≤ 0.001. Serum VLDL and HDL levels were not significantly different between the two groups.Conclusion: Research has suggested that individuals who have contracted COVID-19 have shown a decrese in lipid profile values compared to those who have not been affected by the virus.